Are they there yet? Linkage of patients with tuberculosis to services for tobacco cessation and alcohol abuse - a mixed methods study from Karnataka, India - Nagendra Navya; Kathiresan Jeyashree; Akshaya Kibballi Madhukeshwar; Tanu Anand; Abhay Subashrao Nirgude; Badarudeen Mohammad Nayarmoole; Petros Isaakidis (BMC, 2019)
Abstract Background Tobacco use and alcohol abuse are associated with higher risk of tuberculosis (TB) infection, progression to active TB and adverse treatment outcomes among patients with TB. Revised National Tuberculosis Control Programme (RNTCP) treatment guidelines (2016) require the documentation of tobacco and alcohol use among patients with TB and their linkage to tobacco and alcohol abuse treatment services. This study aimed to assess the extent of documentation of tobacco and alcohol usage data in the TB treatment card and to explore in-depth, the operational issues involved in linkage. Methods A convergent parallel mixed methods study was conducted. All new TB treatment cards of adult patients registered under RNTCP between January and June 2017 in Dakshina Kannada district were reviewed to assess documentation. Document review was done to understand the process of linkage (directing patients to tobacco and alcohol abuse treatment services). In-depth interview of health care providers (n = 7) and patients with TB (n = 5) explored into their perspectives on linkage. Results Among 413 treatment cards reviewed, tobacco use was documented in 322 (78%), of whom 86 (21%) were documented as current tobacco users. Sixteen (19%) out of these 86 patients were linked to tobacco cessation services. Alcohol usage status was documented in 319 (77%) cards of whom 71(17%) were documented as alcohol users. Eleven (16%) out of these 71 patients were linked to alcohol abuse treatment services. The questions in the treatment card lacked clarity. Guidelines on eliciting history of substance abuse and criteria for linkage were not detailed. Perceived enablers for linkage included family support, will power of the patients and fear of complications. Challenges included patient's lack of motivation, financial and time constraints, inadequate guidelines and lack of co-ordination mechanisms between TB programme and tobacco/alcohol abuse treatment services. Conclusion Documentation was good but not universally done. Clear operational guidelines on linkage and treatment guidelines for health care providers to appropriately manage the patients with comorbidities are lacking. Lack of coordination between the TB treatment programme and tobacco cessation as well as alcohol treatment services was considered a major challenge in effective implementation of the linkage services.